Adsorption studies of the hybrid material obtained from the functionalization of silica with alfa and gamma cyclodextrins - Carvalho, Lucas Braganca [UNESP]; Baracho, Raphaela do Vale; Andrade, Jessica Moreira; Magriotis, Zuy Maria; Pinto, Luciana Matos Alves (Taylor & Francis Inc, 2022)
The generation of residues containing dyes by industrial sectors has been mobilizing scientists to develop methodologies capable of treating water containing these contaminants. Adsorption is an option to remove these molecules from the aqueous medium and, for this study, the composites between silica and cyclodextrins alpha (alpha-CDSI) and gamma (gamma-CDSI) were used to capture methylene blue. Adsorption was spontaneous for both composites (Delta G < 0) and characterized as exothermic and of a physical nature, with Delta H of -17.68 and -12.13 kJ mol(-1) for alpha-CDSI and gamma-CDSI, respectively. Adsorption took place over a wide pH range, with an efficiency of approximately 96%, reaching equilibrium at 5 minutes. The adsorption kinetics was described by the pseudo-second-order model (R-2 > 0.999) and the adsorption isotherms showed that the process must occur mainly by dye complexation in the cyclodextrins cavities. The q(m) values obtained were 210.8 and 205.2 mg g(-1) for alpha-CDSI and gamma-CDSI, respectively; the Sips and Temkin models were the ones that best fit the experimental data. The deposition and interactions of the dye with the adsorbent surface were confirmed by the analysis of the IR spectra. Desorption studies showed that the material maintained its adsorption capacity of around 90% until the fourth adsorption/desorption cycle. Thus, the materials produced showed to efficiently remove methylene blue and that composite reuse is a viable process for application in dye removal.
Keywords: Removal; Inclusion complexes; Kinetic; Isotherm; Dye; Methylene blue